2007
DOI: 10.2478/s11686-007-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecological study of the wood mouse helminth community in a burned Mediterranean ecosystem in regeneration five years after a wildfire

Abstract: Parasites are used as biological tags in environmental impact studies. However, terrestrial systems in general and small mammals in particular are rarely considered in these ecological studies. Based on the effects of a wildfire which occurred in the Spanish Serra Calderona Natural Park -a typical Mediterranean ecosystem -the regeneration process of the wood mouse population and its helminth community is analysed. A total of 217 individuals of Apodemus sylvaticus were studied in a five year period, from the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 41 publications
8
42
7
Order By: Relevance
“…Among these perturbations, fires are considered as essential components of the dynamics of Mediterranean-type ecosystems (Moreno & Oechel, 1994), altering species composition and abundance of several species of animals and plants (Trabaud & Prodon, 1993;Terrades, 1996, and references therein). Parasites have been recognized as indicators (or biological tags) for natural or man-induced environmental stress and perturbation (Galán-Puchades & Fuentes, 1996;Marcogliese & Cone, 1997), tracking the effects of human impacts on the environment (Lafferty, 1997). This interesting property of parasites relies on the strict dependence of their hosts , and the response of the intermediate and final hosts to fire will determine the presence of parasites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these perturbations, fires are considered as essential components of the dynamics of Mediterranean-type ecosystems (Moreno & Oechel, 1994), altering species composition and abundance of several species of animals and plants (Trabaud & Prodon, 1993;Terrades, 1996, and references therein). Parasites have been recognized as indicators (or biological tags) for natural or man-induced environmental stress and perturbation (Galán-Puchades & Fuentes, 1996;Marcogliese & Cone, 1997), tracking the effects of human impacts on the environment (Lafferty, 1997). This interesting property of parasites relies on the strict dependence of their hosts , and the response of the intermediate and final hosts to fire will determine the presence of parasites.…”
Section: Introductionmentioning
confidence: 99%
“…This interesting property of parasites relies on the strict dependence of their hosts , and the response of the intermediate and final hosts to fire will determine the presence of parasites. In the Mediterranean Region, helminths of small mammals have been used as models of the post-fire recolonization process (Feliu et al, 1993;Fuentes et al 1998Fuentes et al , 2005Fuentes et al , 2007Fons et al, 1988;Galán-Puchades et al, 1999;Prodon et al, 1987;Torres et al, 1992). Despite most studies did not find differences in the helminth species composition of control and post-fire stages shortly after fire, some authors suggested a decrease in helminth species richness in post-fire areas compared to unburned areas (Feliu et al, 1993;Fuentes et al, 1998Fuentes et al, , 2007Torres et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with these cyclic and long-term investigations, our results take on a preliminary character. Most papers describing the parasite fauna of rodents representing the genus Apodemus pertain to A. sylvaticus (Behnke et al, 1999;Abu-Madi et al, 2000;Fuentes et al, 2007). So far only a study from Germany (Klimpel et al, 2007) refers to the parasites of A. flavicollis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on the parasite fauna of rodents concerning various aspects, such as the impact of extrinsic and intrinsic factors on helminth interactions, have been carried out in recent years (Bajer et al, 2005;Behnke et al, 2005;Eira et al, 2006;Fuentes et al, 2007). Apart from ecological aspects, relevant information about the taxonomical status or host-parasite relationship became apparent during investigations on the helminth fauna of rodents (Feliu et al, 2000;Hildebrand et al, 2004;Hildebrand et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Its intermediate hosts are mainly arvicoline and murine rodents. In Europe, adults of this species have been recorded, usually with low prevalence, in Martes martes (pine marten), Martes foina (stone marten) and Mustela putorius (European polecat) [1][2][3], while Clethrionomys glareolus (bank vole), Microtus agrestis (field vole), Apodemus sylvaticus (wood mouse) and Ondatra zibethicus (muskrat) act as intermediate hosts [3][4][5]. Higher prevalence has been recorded in M. martes in Spain (5.88%) [3] and in O. zibetichus in Belgium (22.2%) [5].…”
Section: Introductionmentioning
confidence: 99%